2022
DOI: 10.1111/tbed.14626
|View full text |Cite
|
Sign up to set email alerts
|

Is vertical transmission the only pathway for Rickettsia felis ?

Abstract: The genus Rickettsia encompasses several species grouped into two main clusters, Typhus and the Transitional groups. The latter group contains Rickettsia felis, an endosymbiont of several arthropods with an uncertain human pathogenicity and whose most efficient transmission mechanism described thus far is transovarial. The aim of this study was to evaluate whether this pathway exists using phylogenetic analysis and partial sequences of the 17kDa and gltA genes and comparing them with host phylogeny using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Groups of ectoparasites by close contact during feeding on the vertebrate. These findings support the recent proposal that cofeeding is the transmission mechanism that allows this microorganism to spread between groups of phylogenetically distant arthropods (Colunga‐Salas et al, 2022). In a recent experimental study carried out on dogs in Australia, R. felis was the cause of a febrile illness that did not compromise the life of the host, demonstrating persistent rickettsaemia that can infect pathogen‐free fleas.…”
Section: Discussionsupporting
confidence: 91%
“…Groups of ectoparasites by close contact during feeding on the vertebrate. These findings support the recent proposal that cofeeding is the transmission mechanism that allows this microorganism to spread between groups of phylogenetically distant arthropods (Colunga‐Salas et al, 2022). In a recent experimental study carried out on dogs in Australia, R. felis was the cause of a febrile illness that did not compromise the life of the host, demonstrating persistent rickettsaemia that can infect pathogen‐free fleas.…”
Section: Discussionsupporting
confidence: 91%
“…The second mechanism is much more feasible, since previous studies in populations of D. marsupialis in the southwestern United States as well as in central Mexico have shown infestations by the cat flea C. felis felis , which have a high prevalence of infection with the flea‐borne rickettsias R. typhi and R. felis (Blanton et al, 2016, 2022; Santoyo‐Colin et al 2021). Therefore, it is plausible that O. puertoricensis could acquire this microorganism by co‐feeding with fleas infected with R. felis (Colunga‐Salas et al, 2022; Serpa et al, 2021). Although in the present study fleas were not observed from the analysed hosts, it cannot be ruled out that they had not been present on the host although it was still alive.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, Brazil, and Mexico, several surveillance studies have been reported that these mammals carry a wide range of ectoparasites infected with various species of Rickettsia , such as Rickettsia rickettsii Brumpt and Rickettsia typhi (Wolbach and Todd) (Blanton et al, 2016; Santoyo‐Colin et al 2021; Serpa et al, 2021). Because marsupials can present massive infestations by other groups of hematophagous arthropods such as the cat flea Ctenocephalides felis felis Siphonaptera: Pulicidae (Bouche), it is possible to suspect that several flea‐borne Rickettsia such as R. typhi and R. felis can be transmitted by cofeeding to other hematophagous arthropods (such as ticks) that feed simultaneously and in close proximity to the infected competent vector (Colunga‐Salas et al, 2022; Fongsaran et al, 2022). Additionally, experimental studies have shown that these mammals exhibit high rickettsemia, for which various groups of hematophagous arthropods can become infected by feeding on these hosts (although they are not necessarily competent vectors) (Blanton et al, 2022; Horta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%